Forensic Human Identification for Cutaneous Microbiome, a Brief Review - Novaes, Natasha R.F.; Fensterseifer, Isabel C. M.; Martins, José L. R.; Silva, Osmar N. (Fronteira: Journal of Social, Technological and Environmental Science, 2021)
Forensic Science compounds many study areas in context of solving crimes, one of which is the forensic microbiology. Combined with genomic approaches, microbiology has shown strong performance in studies regarding the relationship between microorganisms present on human skin and environment. The Human Microbiome Project (HMP) has contributed significantly to characterization of microbial complexity and their connection to human being. The purpose of this work consists of a historical overview of scientific articles, demonstrating the growth and possibility of using skin microbiome in forensic identification. Studies about use of cutaneous microbiome in human identification, as well its forensic approaches, were looked into for writing of this review. Comparisons among cutaneous microbial communities and manipulated objects have been tested using 16S rRNA, as well as a thorough sequencing of the bacterial genome. From use of ecological measures of distance to genetic markers with nucleotide variants and predictive algorithms, research has shown promising results for advances in field of forensic identification. The development of metagenomic microbial panel markers, named hidSkinPlax for targeted sequencing has been designed and tested with great results. Research results show satisfactory potential in human identification by cutaneous microbiome and the possibility for contributive use in elucidating crimes.